2019
DOI: 10.1136/bmjgh-2019-001834
|View full text |Cite
|
Sign up to set email alerts
|

‘It was a ravage!’: lived experiences of epidemic cholera in rural Haiti

Abstract: IntroductionA cholera epidemic began in Haiti over 8 years ago, prompting numerous, largely quantitative research studies. Assessments of local ‘knowledge, attitudes and practices’ relevant for cholera control have relied primarily on cross-sectional surveys. The voices of affected Haitians have rarely been elevated in the scientific literature on the topic.MethodsWe undertook focus groups with stakeholders in the Artibonite region of Haiti in 2011, as part of planning for a public health intervention to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…As far as the most recent pandemics such as the H1N1 and the current COVID-19 are concerned, review of empirical studies about lived experiences using phenomenology as a research approach mostly focused on allied medical fields as well as school job context (e.g. Corley et al, 2010;Guillaume et al, 2019;Howard & Howard, 2012;Raymond et al, 2019;Van et al, 2010;Wang et al, 2020). However, of equal interest, is the need to account for the lived experiences of a vulnerable group of stranded students who are at risk of psychosocial pressures.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the most recent pandemics such as the H1N1 and the current COVID-19 are concerned, review of empirical studies about lived experiences using phenomenology as a research approach mostly focused on allied medical fields as well as school job context (e.g. Corley et al, 2010;Guillaume et al, 2019;Howard & Howard, 2012;Raymond et al, 2019;Van et al, 2010;Wang et al, 2020). However, of equal interest, is the need to account for the lived experiences of a vulnerable group of stranded students who are at risk of psychosocial pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our data show that on three of four questions, respondents for PLOS NEGLECTED TROPICAL DISEASES children with diarrhea demonstrated similar or even greater levels of knowledge than respondents for children without diarrhea. Our group's previous work demonstrated that other factors, such as financial constraints and lack of access to sanitation products, limited respondents' ability to put their knowledge into practice [42,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…The second article was published in 2019 but the data was collected in 2011 as part of planning a public health initiative. (33) The other three articles all focused on knowledge, attitudes and practices (KAP) related to water, sanitation and hygiene (WASH) in the midst of the cholera outbreak. (34)(35)(36) Thus, the existing body of research about the cholera outbreak lacks empirical documentation of the experiences and perceptions of Haitian community members themselves.…”
Section: Purposementioning
confidence: 99%
“…(55) These statistics are signi cantly lower than the averages for Latin America and the Caribbean at 90% and 80% respectively (55). (33,44) When one considers the millions of dollars in aid, development and re-building that has been pledged to Haiti since the January 2010 earthquake and the start of cholera epidemic, it is perplexing that so many Haitians are still without clean water and sanitation. By increasing focused efforts to strengthen water and sanitation infrastructure in Haiti, the UN would not only be keeping its prior commitment to the Haitian people, but it would also be a taking tremendous step towards meeting Sustainable Development Goal (SDG) 6 -clean water and sanitation for all, as well as SDG 3 -good health and wellbeing for all.…”
Section: Un Responsementioning
confidence: 99%